Tumada Peak Drinking Water Supply System Plan (SPAM) Tumada Village is Located in The Kapontori District of The Buton Regency - Asrasal, Aswad; Abdu, Muhammad; Musrifin, Musrifin; Hafsyah, Intan Ahlul (Room of Civil Society Development, 2022)
The community service program's objective is to apply technical knowledge, particularly civil engineering, to the village government and the local population. So they may appreciate the critical nature of discussion and consultation over image design during the Planning for Drinking Water Supply System (SPAM) phase prior to construction. The program's implementation is supposed to result in a design that is responsive to the needs and conditions of the surrounding environment. To accomplish this, effective design concepts and mentorship methods are employed to provide consulting services to the village administration and community, ensuring that the program's objectives are realized. The final results acquired include the design and budget for the Puncak Tumada Drinking Water Supply System (SPAM) in Tumada Village, Kapontori District, Buton Regency.